Evidenciação do estado da arte do tema “Sistema Integrado de Gestão Analisado sob a Ótica de seu Desempenho” - Ensslin, Sandra Rolim; Ensslin, Leonardo; Rosário, Alexandre Turazzi do; Pereira, Vera Lucia Duarte do Valle (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The paradigm shift in the market in different fields has been encouraging companies to seek different ways to manage their activities. Management models are widely used a tool to improve product quality, the health and safety of the company employees as well as the environment in which the organization operates. However, when setting up this systems, organizations usually observe only the individual requirements of the standards, leaving out relevant information from the inside context. In addition to generating a large number of redundant documents, this situation ends up causing an overload in the activities of employees, making it difficult to manage these systems. One possible solution to manage these problems is integrating different systems, where one observes the similarities between them to facilitate their implementation, operation and planning. The aim of this article of exploratory-descriptive nature is to research in the literature in order to find a relevant biographic portfolio, coherent to the researcher’s point of view on the subject, thereby producing more knowledge to the researchers through Bibliometric Analysis of the international literature, by using the Knowledge Development Process – Construtivist (ProKnow-C) as an intervention tool.